Teaching Xitsonga home language reading in Grade 8 at Shiluvane Circuit, Mopani West District, Limpopo Province, South Africa - Makhubele, Gezani Caswell (My University, 2024)
The primary objective of this study was to investigate the challenges encountered by Grade 8 teachers when teaching reading in the Xitsonga Home Language at Shiluvane Circuit in the Mopani West District, Limpopo province in South Africa. The study holds significance as many students in the participating schools exhibit little to no interest in reading for pleasure, often perceiving reading as solely a study tool. A qualitative approach was employed to explore the difficulties experienced by intermediate teachers when teaching reading. Data were gathered through semi-structured interviews, observations, and writing tasks, and analysed thematically within an interpretive paradigm. The study utilised the Psycholinguistic Theory as a framework to comprehend why learners struggle with reading and to ascertain if learners possess the necessary prior knowledge of the text they read in the classroom. The study's findings suggest that establishing community libraries positively fosters a reading culture. The study further revealed that teachers face significant challenges in teaching reading. The study recommends that regular workshops be conducted to equip subject advisors with effective reading strategies that can be used to support educators.
Thesis (M. Ed.) -- University of Limpopo, 2024
Keywords: Teachers; Teaching; Reading; Comprehension; Reading comprehension language; Home language; Xitsonga home language; High school teachers -- Books and reading -- South Africa; Reading comprehension -- Study and teaching; Tsonga language -- Study and teaching; Reading (Secondary)